HLA class II polymorphism in Latin American patients with multiple sclerosis (2010)
Objective: To identify HLA-DRB1 alleles contributing to susceptibility to multiple sclerosis (MS) in a Colombian population and to estimate the common effect size of HLA class II on MS susceptibility in Latin American populations through a meta-analysis. Methods: A total of 65 Colombian patients with MS and 184 matched controls were included. HLA-DRB1 typing was done using the sequence-specific oligonucleotide probe method. A bivariate and a multivariate logistic regression analyses were done. Case-control studies performed in Latin America were searched up to January 2009 through a systematic review of the literature. Effect summary odds ratios (ORs) and 95% confidence intervals (CIs) were obtained by means of the random effect model. Results: A total of 464 cases and 2581 controls from 7 studies and the results of the present study in Colombians were analyzed. HLA-DRB1*15 (OR: 2.3; 95% CI: 1.68-3.07; p and lt; 0.001) and HLA-DQB1*06 (OR: 2.2; 95% CI: 1.54-3.07; p and lt; 0.001) groups as well as DRB1*1501 (OR: 2.6; 95% CI: 1.67-4.02; p and lt; 0.001), DRB1*1503 (OR: 2.2; 95% CI: 1.39-3.62; p = 0.001) and DQB1*0602 (OR: 2.5; 95% CI: 1.66-3.71; p and lt; 0.001) alleles were found to be risk factors for MS. The myelin basic protein immunodominant sequence 221VHFFKNIVT229 was predicted to strongly and simultaneously bind to HLA-DRB1*1501 and *1503. Conclusion: The current study highlights the effect size of HLA class II in MS in Latin America and confirms similar allelic risk factors across diverse populations. Receptor-ligand interactions in the HLA-antigenic peptide complex could have potential predictive and therapeutical implications. © 2009 Elsevier B.V. All rights reserved.